Multi-drug cocktails: Impurities in commonly used illicit drugs seized by police in Queensland, Australia. (1st August 2019) - Peck, Yoshimi; Clough, Alan R.; Culshaw, Peter N.; Liddell, Michael J.
Highlights: Illicit drugs seized by police were mainly methamphetamine, MDMA and cocaine. Cocaine, 2C-B and GHB were more frequently adulterated with other substances. Methamphetamine, MDMA, THC and heroin samples showed high purity. Methamphetamine and MDMA contained also the largest variety of impurities. Emerging NPS as adulterants are similar to that reported in Europe. Abstract: Background: Impurities in commonly used illicit drugs raise concerns for unwitting consumers when pharmacologically active adulterants, especially new psychoactive substances (NPS), are used. This study examines impurities detected in illicit drugs seized in one Australian jurisdiction. Methods: Queensland Health Forensic and Scientific Services provided analytical data. Data described the chemical composition of 9346 samples of 11 illicit drugs seized by police during 2015-2016. Impurities present in primary drugs were summarized and tabulated. A systematic search for published evidence reporting similar analyses was conducted. Results: Methamphetamine was the primary drug in 6608 samples, followed by MDMA (1232 samples) and cocaine (516 samples). Purity of primary drugs ranged from ∼30% for cocaine, 2-CB and GHB to >90% for THC, methamphetamine, heroin and MDMA. Methamphetamine and MDMA contained the largest variety of impurities: 22 and 18 variants, respectively. Drug adulteration patterns were broadly similar to those found elsewhere, including NPS, but in some primary drugs impurities were found which had not been reported elsewhere. Psychostimulants were adulterated with each other. Levamisole was a common impurity in cocaine. Psychedelics were adulterated with methamphetamine and NPS. Opioids were quite pure, but some samples contained methamphetamine and synthetic opioids. Conclusions: Impurities detected were mostly pharmacologically active adulterants probably added to enhance desired effects or for active bulking. Given the designer nature of these drug cocktails, the effects of the adulterated drugs on users from possible complex multi-drug interactions is unpredictable. Awareness-raising among users, research into complex multi-drug effects and ongoing monitoring is required.